Environmental Concern Priming and Social Acceptance of Sustainable Technologies: The Case of Decentralized Wastewater Treatment Systems - Gómez-Román, Cristina; Sabucedo, José-Manuel; Alzate, Mónica; Medina, Beatriz (Frontiers in Psychology, 2021)
According to a report by the World Economic Forum, the water crisis is the fourth most serious global risk to society. The apparent limitations of the hydraulic paradigm to solving this crisis are leading to a change in water management approaches. Recently, decentralized wastewater treatment systems have re-emerged as a partial solution to this problem. However, to implement these systems successfully, it is necessary not only to design this technology, but also to have social support and willingness among citizens to use it. Previous studies have shown that these technologies are often perceived as being too costly, and people often do not consider the need for adopting them. However, it has also been pointed out that thinking about these technologies as a sustainable endeavor to reduce human impact on the environment can help overcome the barriers to usage. Thus, we test whether priming environmental concerns before presenting information about decentralized wastewater treatment plants will increase acceptance of those technologies. In this study, we test whether priming environmental concerns can enhance acceptance of decentralized wastewater treatment plants even when presenting disadvantages of the technology. In order to do so, we designed an experimental study with a sample of 287 people (85.7% women, M age = 20, 28). The experimental design was a 2 (priming the environmental concern vs. no priming) x 2 (type of information: only advantages vs advantages and disadvantages). The results showed that those in the environmental concern priming condition had more positive attitudes and behavioral intentions towards decentralized wastewater treatment plants than those in the control condition group. Participants who received only advantages information had a more positive perception towards the decentralized wastewater systems than in the condition where disadvantages were present, but in the priming condition this difference was not significant. Which implies that priming environmental concern helps to overcome the possible disadvantages that act as barriers to acceptance.